Efforts To Prevent Anemia In Pregnant Women - Nurmaliza, Lili; Fitriani, Enny; -, Andilala; -, Ruseni (Universitas Prima Indonesia, 2025)
Anemia in pregnancy is a condition in which the mother has a hemoglobin level below 11 gr% in the first and third trimesters or a level of <10.5 gr% in the second trimester. The limit value and its difference with the condition of non-pregnant women is hemodilution, especially in the second trimester. Sulistyawati (2019). Anemia in pregnant women is generally caused by physiological changes during pregnancy and is influenced by malnutrition. The anemia that is often found in pregnancy is due to iron deficiency. This occurs because of the increased need for iron to supply the fetus and placenta, in order to enlarge tissue and red blood cell mass. The impact of anemia on pregnant women can cause obstacles to fetal growth, both body cells and brain cells, abortion, long labor due to lack of uterine thrust, bleeding, and infection (Septiyaningsih R, Indratmoko S, 2019). The population in this study were pregnant women with a total of 38 respondents who visited the Mardianum clinic, with the results obtained efforts to prevent anemia with compliance with taking FE tablets, 11 people who were not anemic were compliant, 29% and 4 people who were anemic were compliant, 10.5%, and based on non-compliance with taking FE tablets, 2 people who were not anemic were 5.2% and 21 people who were anemic 55.3%. With a P Value of 0.000, which means that there is a relationship between compliance with taking FE Tablets and the occurrence of anemia. Where it is expected that all pregnant women will be compliant in consuming FE tablets to prevent anemia.